Measuring Preschool Teachers' Social-emotional Practices: A Comparison of Two Measures. Issue 2 (17th February 2022) - Rojas, Natalia M; Mattera, Shira; Morris, Pamela; Raver, Cybele
ABSTRACT: Research Findings : Evidence suggests that teachers are effective at improving the social and emotional readiness of low-income children. However, few measures are available to assess teachers' use of specific social-emotional practices within their classrooms. This paper compares an observational measure of teachers' social-emotional practices, the Adapted Teacher Style Rating Scale (TSRS), to an instrument of general classroom climate within a randomized control trial, including 307 Head Start classrooms across the country. Results confirmed the expected underlying three-factor structure of the Adapted-TSRS across mixed-age and 4-year-old only Head Start classrooms. The measure was found to have good internal consistency, reliability, and acceptable concurrent correlations with other previously validated observational measures of classroom climate. Policy or Practice : The results support the usefulness and added value of a more specific observational measure of teachers' social-emotional practices.